2017
DOI: 10.1007/s13593-017-0467-1
|View full text |Cite
|
Sign up to set email alerts
|

Soil solarization as a sustainable solution to control tomato Pseudomonads infections in greenhouses

Abstract: The reduction or phase-out of soil fumigants according to European directives has led to a re-evaluation of sustainable heat-based techniques and exploiting solar energy, e.g., solarization that was used successfully for the eradication of fungi, weeds, and nematodes. Since the beginning of the current century, bacterial infections caused by phytopathogenic Pseudomonads have been increasingly reported as threat for many horticultural crops worldwide. Nowadays, this disease represents a limiting factor for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…Apart from using chemical disinfectants, researchers recently explored alternative methods for disinfecting items potentially contaminated by the novel coronavirus, including ultraviolet irradiation (Zhao et al 2020), ozonation (Blanchard et al 2020) and electrical heating (Oh et al 2020). As Nature's biocide, solar radiation disinfects microorganisms via heat and ultraviolet radiation (Castello et al 2017). Since ancient times, these benefits have been exploited by humankind for water sanitation (Rijal and Fujioka 2001) and more recently for pollutant degradation (Mecha and Chollom 2020; Mousset and Dionysiou 2020) and green synthesis (Patel et al 2020;Srivastava et al 2020).…”
Section: Solar Heating As a Passive Strategy For Disinfecting Covid-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from using chemical disinfectants, researchers recently explored alternative methods for disinfecting items potentially contaminated by the novel coronavirus, including ultraviolet irradiation (Zhao et al 2020), ozonation (Blanchard et al 2020) and electrical heating (Oh et al 2020). As Nature's biocide, solar radiation disinfects microorganisms via heat and ultraviolet radiation (Castello et al 2017). Since ancient times, these benefits have been exploited by humankind for water sanitation (Rijal and Fujioka 2001) and more recently for pollutant degradation (Mecha and Chollom 2020; Mousset and Dionysiou 2020) and green synthesis (Patel et al 2020;Srivastava et al 2020).…”
Section: Solar Heating As a Passive Strategy For Disinfecting Covid-1mentioning
confidence: 99%
“…In agronomy, soil solarization has been used for the inactivation of pathogens and weeds by placing plastic films on moist soils when the ambient temperature is high. Direct thermal inactivation is thought to be the principal mechanism in such process (Addabbo et al 2010;Castello et al 2017). During the current pandemic, solar-based disinfection has the potential to be utilized as a convenient passive approach for inactivating SARS-CoV-2 in large enclosed objects with complex interior structures that may be particularly challenging for performing chemical disinfection.…”
Section: Solar Heating As a Passive Strategy For Disinfecting Covid-1mentioning
confidence: 99%
“…Procedures for making substrates at local sites include: (a) from crop straw to fermentation to the final substrate product, and (b) the potential reuse of the substrate after restoration of the nutrient content light utilization (Cuce et al 2016). Use of solar energy for greenhouse crop production has made progress in many areas/countries (Farjana et al 2018), including Australia, Japan (Cossu et al 2017), Israel (Castello et al 2017), and Germany (Schmidt et al 2012), as well as developing countries such as Nepal (Fuller and Zahnd 2012) and India (Tiwari et al 2016). In China, the installation of modern solar modules is expensive at present, with an estimated payback period of 9 years (Wang et al 2017).…”
Section: Increased Energy Use Efficiencymentioning
confidence: 99%
“…Wu et al [37] and Wang et al [38] stated that mulching applications are significantly influenced by an increase in the soil temperature through a thermal transfer between the ambient surroundings and the soil. For example, the soil temperature is considerably influenced by the color and number of layers of mulch [39,40]. Moreover, as other authors have recently demonstrated, the application of catch crops, straw mulches, or plastics reduces the soil erosion rate by several orders of magnitude [41,42].…”
Section: Introductionmentioning
confidence: 97%